Application of marine-derived polysaccharides as immunostimulants in aquaculture: A review of current knowledge and further perspectives. Issue 86 (March 2019) - Mohan, Kannan; Ravichandran, Samuthirapandian; Muralisankar, Thirunavukkarasu; Uthayakumar, Venkatachalam; Chandirasekar, Ramachandran; Seedevi, Palaniappan; Abirami, Ramu Ganesan; Rajan, Durairaj Karthick
Abstract: The use of antibiotics in the feeds of cultivable aquatic animals has been generally practised to reduce infectious diseases as well as to improve the survival and growth. In recent years, many countries ban to aquatic animals due to the use of large amount of antibiotics and chemotherapies, thus alternative novel strategies are need to promote the growth of aquatic animals and control the pathogens. Dietary supplementation of marine-derived polysaccharides (MDPs) is one of the potential substitutes for antibiotics in aquatic animal feeds. Recently, the use of dietary MDPs in the aquaculture animals has been focused with much interest. In aquaculture, MDPs are used as prebiotic substance which is mostly accepted as a nutritional component for improving the growth performance and health conditions. Hence, present review is a comprehensive and an updated collection of available research reports on different MDPs (alginate, fucoidan, carrageenan, laminarin, ulvan, galactan, agar, chitin and chitosan), route of administration, dosage and applications for improving aqua feeds with emphasis on its effects on growth, biochemical indices, immune response, gut microbiota and disease resistance of aquaculture animals. This review describes the sustainability of global aquaculture production by providing a best alternative to harmful antibiotics, thereby meeting the emerging consumer demand for antibiotic-free aquatic food products. Graphical abstract: Image 1 Highlights: Application of MDPs as immunostimulants in aquatic animals was investigated. Dietary MDPs can enhance growth and innate immune responses of aquatic animals. Dietary MDPs can enhance the ability of aquatic animals to resistance the infection.